2015
DOI: 10.1039/c5cc04708k
|View full text |Cite
|
Sign up to set email alerts
|

Rh-catalyzed sequential oxidative C–H activation/annulation with geminal-substituted vinyl acetates to access isoquinolines

Abstract: The concise synthesis of 3-substituted or non-C3-substituted isoquinolines through Rh-catalyzed sequential oxidative C-H activation/annulation with geminal-substituted vinyl acetates was developed with good functional group tolerance. The protocol was successfully applied to the total synthesis of the natural product papaverine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 90 publications
(33 citation statements)
references
References 41 publications
0
33
0
Order By: Relevance
“…Based on the detailed mechanistic studies, authors have formulated the reaction mechanism which is in agreement with the conventional Rh-catalysis (Scheme 213). [225] Again in 2018, Webb et al described Rhodiumcatalyzed isoquinoline synthesis which is similar to the previously reported method by Chu et al [194] The method relies on CÀ H activation/annulation strategy using vinyl acetate 321 as an acetylene equivalent. The methods holds good for wide range of substrates by giving good yields (Scheme 214).…”
Section: Rh-catalyzed Isoquinoline Synthesismentioning
confidence: 69%
See 1 more Smart Citation
“…Based on the detailed mechanistic studies, authors have formulated the reaction mechanism which is in agreement with the conventional Rh-catalysis (Scheme 213). [225] Again in 2018, Webb et al described Rhodiumcatalyzed isoquinoline synthesis which is similar to the previously reported method by Chu et al [194] The method relies on CÀ H activation/annulation strategy using vinyl acetate 321 as an acetylene equivalent. The methods holds good for wide range of substrates by giving good yields (Scheme 214).…”
Section: Rh-catalyzed Isoquinoline Synthesismentioning
confidence: 69%
“…[193] In 2015, Chu et al described the synthesis of 3substituted or non-C3-substituted isoquinolines 2 from O-acetyl oxime 68 and geminal-substituted vinyl acetates 321 through rhodium catalyzed sequential oxidative CÀ H activation/annulation strategy (Scheme 191). [194] The developed method was realized under [Cp*RhCl 2 ] 2 and Ag catalyzed reaction conditions to obtain corresponding isoquinolines up to 90% yield. Under the optimized reaction conditions, O-acetyl oxime and vinyl acetates with EDG and EWG gave corresponding isoquinoline in moderate yields.…”
Section: Rh-catalyzed Isoquinoline Synthesismentioning
confidence: 99%
“…While the annulation of aromatic oximes with internal alkynes has been thoroughly investigated for the preparation of 3,4‐disubstituted isoquinolines (Scheme a–i), similar versions with alkenes are rare . Moreover, these transformations focus on special alkenes, including vinyl acetates, 1,3‐dienes and electron‐poor alkenes, which serve as convenient acetylene equivalents for the synthesis of 3‐substituted isoquinolines. Examples that utilize common terminal alkenes as reaction partners towards 3,4‐dihydroisoquinolines have not been reported.…”
Section: Methodsmentioning
confidence: 99%
“…Examples that utilize common terminal alkenes as reaction partners towards 3,4‐dihydroisoquinolines have not been reported. In 2015, the group of Yu/Cheng reported the first rhodium‐catalysed sequential oxidative C−H activation/annulation of aromatic oxime esters with vinyl acetates leading to 3‐substituted or non‐C3‐substituted isoquinolines (Scheme a–ii). The group of Glorius has developed a PivOH‐promoted Rh(III)‐catalysed redox‐neutral C−H activation/cyclization/isomerization strategy for achieving [4+2] annulation of aromatic oxime esters and diverse 1,3‐dienes towards 3‐alkyl‐substituted isoquinolines (Scheme a–iii).…”
Section: Methodsmentioning
confidence: 99%
“…Subsequently, Yu and Cheng reported that internally-substituted vinyl acetates react with acetophenone oxime esters under rhodium catalysis facilitating access to 3-substituted quinolines. 27 In this paper, they also disclosed that vinyl acetate itself could be used as a reagent, generating 3,4-unsubstituted isooquinolines, exemplified in a synthesis of the alkaloid papaverine. This prompts us to report our own work on the use of vinyl acetate as an acetylene equivalent in the synthesis of isquinolines (Scheme 1b).…”
Section: Introductionmentioning
confidence: 94%